Implikasi Revolusi Sains Thomas S. Khun dalam Media Dakwah - Kurniawan, Fajar Adhi (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
Thomas Khun in his book The Structure of Scientific Revolutions argues that the paradigm shift from the old paradigm to the new paradigm produces scientific breakthroughs that are revolutionary, both partially and thoroughly. The paradigm shift occurs in several stages before the new paradigm replaces the previous paradigm. Islam continues to spread its teachings through various means, including utilizing electronic media such as radio and television. The shift to digital da'wah media affects the way da'wah activists organize, distribute and manage religious messages. This research is library research, which is research that uses literature in the form of books, articles, and the like. The result of this article is that a shift in the point of view or paradigm of da'wah media will occur when digital da'wah media proves to be more effective in achieving da'wah goals and can well meet the needs of the audience. This new paradigm is the result of the application of information and communication technology that is more interactive, participatory and decentralized in the dissemination of religious messages.